Uncertainties of Trade Environment, Market Economy Status, and Anti-Dumping Investigations—Evidence from China. Issue 7 (28th May 2022) - Liu, Li-Jun; Zhang, Jing-qi
ABSTRACT: Based on the in-depth analysis of the characteristics of anti-dumping investigations against China from the industry and country concentration degree, this paper finds that NES countries were still the main initiators of anti-dumping investigations, and the industrial sector was the concentrated area. On this basis, this paper adopts the comprehensive feasible generalized least squares method and negative binomial regression to empirically examine factors in anti-dumping investigations against China. The results show that market economic status is not the most critical factor in anti-dumping investigations against China, and the domestic economic situation of importers has a stronger impact.